Copper sulfate induces clinico-hematological, oxidative stress, serum biochemical and histopathological changes in freshwater fish rohu (Labeo rohita) - Naz, Saima; Hussain, Riaz; Guangbin, Zhang; Chatha, Ahmad Manan Mustafa; Rehman, Zia Ur; Jahan, Shfaq; Liaquat, Momil; Khan, Ahrar (Frontiers in Veterinary Science, 2023)
Despite being an essential trace element for numerous metabolic processes and micronutrients, copper (Cu) has induced adverse effects on the environment and public health due to its continuous and widespread use for the last several decades. The current study assessed the hematological and histopathological alterations in the freshwater fish (Labeo rohita) exposed to graded concentrations of copper sulfate. For this purpose, L. rohita fish (n = 72), weighing approximately 200-215 g, were randomly divided into four experimental groups and then exposed to acute doses of CuSO4, i.e., control, 0.28, 0.42, and 0.56 μgL-1. For comparative analysis of hematological and biochemical changes, blood/serum samples were obtained on 12, 24, and 36 days. Overall, the body weight of fish decreased with the time and dose of CuSO4; as the dose increases, body weight decreases. Dose and time-dependent results were observed in other parameters also. Results showed a significant increase in white blood cells, whereas red blood cells count, Hb, and Hct were significantly reduced in experimental groups compared to the control. The mean corpuscular hemoglobin (MHC) and mean corpuscular hemoglobin concentration (MCHC) showed a non-significant decrease in the treated groups compared to the control group. Serum biochemical parameters, including total proteins, albumin, and globulin, decreased significantly (p < 0.05). At the same time, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), glucose, and cholesterol were significantly (p < 0.05) increased in the treated groups compared to the control group. Significantly (p < 0.05) increased levels of lipid peroxidation while decreased values of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (RGSH) in the blood of fish were recorded. Histopathological examination of fish gills, liver, and kidneys showed inflammation and degenerative changes due to CuSO4 exposure. In the brain tissue, degenerative changes like neuron necrosis, intracellular edema, cytoplasmic vacuolization, and neural cell congestion were observed. In conclusion, the study indicates that exposure to copper sulfate, even in smaller concentrations, can cause adverse hematological and histopathological changes in L. rohita fish.